Koala immunology and infectious diseases: How much can the koala bear?. (May 2018) - Madden, Danielle; Whaite, Alessandra; Jones, Elizabeth; Belov, Katherine; Timms, Peter; Polkinghorne, Adam
Abstract: Infectious diseases are contributing to the decline of the iconic Australian marsupial, the koala ( Phascolarctos cinereus ). Infections with the obligate intracellular bacteria, Chlamydia pecorum, cause debilitating ocular and urogenital-tract disease while the koala-retrovirus (KoRV) has been implicated in host immunosuppression and exacerbation of chlamydial pathogenesis. Although histological studies have provided insight into the basic architecture of koala immune tissues, our understanding of the koala immune response to infectious disease has been limited, until recently, by a lack of species-specific immune reagents. Recent advances in the characterisation of key immune genes have focused on advancing our understanding of the immune response to Chlamydia infection, revealing commonalities in disease pathologies and immunity between koalas and other hosts and paving the way for the development of a koala Chlamydia vaccine. This review summarises these recent findings and highlights key aspects of the koala immune system requiring further attention with particular regard to their most prominent infectious diseases. Highlights: The koala immune system is as complex as its placental counterparts. Key immunological reagents are becoming available for koalas. Chlamydia pecorum and koala retrovirus are the major pathogens of the koala. Understanding the koala immune response to Chlamydia will continue to aid vaccine development.